Fans and fanfictions, reading, appropriation and production, analyzed from the perspective of reception theory: the case of Game of Thrones and A Song of Ice and Fire - Espinoza Guanilo, Antonio Hector (2021)
This research pretends to analyze the reception of a literary and audiovisual work inside an online fan community and the creation of fan fiction literature by the members of this community, as well as the relationship with the canonical author. Data was collected through the content analysis of the texts written by the fans and the use of a questionnaire fulfilled by the same group. Thanks to this information, and with the help of Reception Theory concepts, it was proved how fans become an active audience that produce new content from the appropriation and resignification of the original text. In addition, it became evident the way they consume the canonical story and how they interact with it and its authors.